Cyber Notary Dalam Pembuatan Akta - Kadir Salmudin, Andi Muhammad; Sakharina, Iin Karita; Arisaputra, Muhammad Ilham (Universitas Widya Gama Malang, 2024)
This study aims to analyze the implementation of cyber notary services in Makassar City and to analyze the inhibiting factors for implementing cyber notary services in making deed in Makassar City. This research is an empirical research type, the location of this research was conducted in Makassar City, South Sulawesi Province. The results of the study show that the application of cyber notary services to date has not had a notary in Makassar City who has made a notary deed using the cyber notary system because a notary does not have the authority granted by law to make it. The authority granted by UUJN is limited to the authority to certify transaction activities between notaries and appearers, including data collection. But not for the Notary's authority as a whole, namely the preparation of authentic deeds or the making of authentic deeds. The existence of legal implications for the delay in implementing cyber notary services is due to the ambiguity of norms (inconsistency) regarding Article 16 paragraph (1) letter m UUJNP 2014 with Article 15 paragraph (3) UUJNP 2014 which has implications for the implementation of a notary's authority such as the application of cyber notary in making deed authentic. Including the existence of several existing laws, namely: Article 1 paragraph (7) UUJN; Article 16 paragraph (1) letter m UUJN; Article 1868 Civil Code; and Article 5 paragraph (4) of the ITE Law which has legal implications for delays in the implementation of cyber notary services. So that if a notary insists on making an authentic deed in a cyber notary way, it will result in the degradation of the authentic deed into an underhanded deed.